Enhancing Diversity in STEMM - Haddad, Mary Alice; Jenkins, Tyler; Solivan, Bonnie; Williams, Alison (Frontiers in Education, 2021)
Professional and scientific societies can foster inclusive environments that can enhance the diversity of their respective fields and disciplines, but some associations are doing a better job than others. This paper offers a comprehensive overview of more than a dozen professional associations and their efforts to support diversity. It finds that resources generally fall into two categories: 1) Websites highlighting the accomplishments of specific individuals, which raise the profile of diverse practitioners in the field. 2) Membership associations that support under-represented communities within a particular field. This article will offer a review of the resources available and some recommendations for how professional associations can better enhance their support for diversity and inclusion in their fields.